River of change (Asian Development Bank, 1995)
For centuries, the Mekong River has enticed emissaries and explorers, travellers, and traders, into the heart of Southeast Asia. Today, in an era of peace, the six Mekong countries are working together in a subregional economic cooperation. Supported by the Asian Development Bank, the cooperation is bringing hope and change to the people of Mekong.